Can Homocysteine Be Used to Identify Vitamin B12 or Folate Deficiencies During Pregnancy in Low Resource Settings?. (7th June 2021) - Amarasinghe, Gayani; Jayasinghe, Imasha; Hettiarachchi, Ayesh; Koralegedara, Iresha; Kappagoda, Chamila; Mendis, Wasana; Agampodi, Thilini; Agampodi, Suneth
Abstract: Objectives: With universal iron supplementation during pregnancy, role of other nutritional causes of anemia such as Vitamin B12 and folate deficiencies are increasingly coming to light. Testing vitamin B12 and folate levels is costly and inconvenient in low and middle income settings. Serum Homocysteine level is proposed as a cheaper and more feasible alternative to indicate vitamin B12/folate deficiency. We evaluated the role of Homocysteine as a predictor of B12/folate level among anaemic pregnant women in Sri Lanka. Methods: We measured fasting serum total Homocysteine in a randomly selected sub sample of anaemic pregnant women (hemoglobin less than 11g/dl) from the Rajarata Pregnancy Cohort (RaPCo), Anuradhapura, Sri Lanka. They were referred to a special hospital clinic for B12 and folate assessment within 2 weeks of the initial assessment. Homocysteine levels > 6.9 µmol/L in first and > 9.6 µmol/L in second trimesters were defined as Hyperhomocysteinaemia. B12 levels below 203 pg/ml and folate levels below 4ng/ml were defined as deficiency. Sensitivity and specificity were calculated and Spearmen correlation was performed. Results: Twenty two anaemic pregnant women in 6 to 18 weeks of gestation were included in the assessment. Median haemoglobin level of the selected sample was 10.2 g/dl (Range 8.2–10.9). Homocysteine (Range 4.43–17, median 8 µmol/L), B12 (Range 149.6–721, median 299.8 pg/ml) and folate (Range 5.5–40, median 16.6 ng/ml) showed skewed distribution. Hyperhomocysteinaemia was observed in 12/22 (50%) pregnant women and B12 deficiency was observed in five participants (22.7% CI 10.1–43.4). None had folate deficiency. Hyperhomocysteinaemia was present in 2/5 (40%) B12 deficient and 10/17 (58.8%) B12 normal participants. Sensitivity of Homocysteine to indicate B12 deficiency was 40% (95% CI 11.8 to 76.9) and specificity was 41.2% (21.6, 67). Predictive values of positive and negative tests were 16.7% and 70% respectively. Homocysteine levels did not correlate with B12 level (Spearmen r = -0.26, p = 0.24) or folate level (spearmen r = 0.04, p = 0.86). Conclusions: Elevated Homocysteine levels cannot be used as a reliable indicator of B12 or Folate deficiency in anaemic pregnant women. Funding Sources: Accelerating Higher Education Expansion and Development (AHEAD) Operation of the Ministry of Higher Education, Sri Lanka.